2022
DOI: 10.1080/0163853x.2022.2050084
|View full text |Cite
|
Sign up to set email alerts
|

Please Join Me/Us/Them on My/Our/Their Journey to Justice in STEM

Abstract: Despite decades of effort to broaden participation in science, technology, engineering, and mathematics (STEM), many fields remain demographically skewed. Marginalized and minoritized people are still underrepresented in and underserved by the sciences. In this paper, the author considers the question, 'How do we improve representation in STEM?' by reflecting on his own journey and themes such as imposter syndrome, decentering, meritocracy, and activism. Importantly, 'underrepresentation' is not a mysterious h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 109 publications
0
9
0
Order By: Relevance
“…The second author was a student enrolled in the course, and identifies as a queer, neurodivergent, disabled person. Both authors are engaged in scholarship and activism regarding DEIB in STEM fields, and have published on these topics (Jennings et al, 2020; Roscoe, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second author was a student enrolled in the course, and identifies as a queer, neurodivergent, disabled person. Both authors are engaged in scholarship and activism regarding DEIB in STEM fields, and have published on these topics (Jennings et al, 2020; Roscoe, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Analyses have observed that engineering training can foster a sense of dissociation between engineering and societal issues—beliefs that engineering is “apolitical,” or that technical and social concerns are separate (Cech, 2014). Similarly, scholars have critiqued how engineering cultures promote “meritocratic” ideas that reward skill and effort without acknowledging the intersectional factors that enable these resources to matter (Roscoe, 2022; Cech, 2014; Farrell et al, 2021; Slaton, 2015). Taken together, such mindsets make it difficult to inspect and challenge systemic discrimination in STEM by casting serious concerns as exaggerated or irrelevant distractions.…”
Section: Introductionmentioning
confidence: 99%
“…He has contributed to equitycentered projects and scholarship across multiple organizations, including the Human Factors and Ergonomics Society (Roscoe et. al., 2019), the Society for Artificial Intelligence in Education (Roscoe et al, 2022), and Society for Text and Discourse (Roscoe, 2022). He is currently funded by the Gates Foundation to study inclusive language analytics and to develop equity-centered chemistry courseware.…”
Section: Who Am I? Who Are You To Even Ask?mentioning
confidence: 99%
“…For example, scholars have called for greater attention to equity, justice, and sociopolitical issues in learning sciences (Guttiérrez & Jurow, 2016; Sungupta-Irving & McKinney de Royston, 2020), data science (Green, 2021; Lewis & Stoyanovich, 2021), artificial intelligence in education (Lewis & Stoyanovich, 2021; Roscoe et al, 2022), and human factors and ergonomics (Roscoe et al, 2019), just to name a few. Such calls have been driven by rising awareness that inattention to DEIB results in potentially harmful outcomes, such as algorithmic bias in educational systems (Baker & Hawn, 2021) and excluding people from (or pushing them out) of relevant fields altogether (Roscoe, 2022).…”
Section: Panel Presentationsmentioning
confidence: 99%